Bagaimana Promosi Penjualan Online dan Atmosfer Web Mempengaruhi Konsumen Muda dalam Pembelian Impuls Online - Bagaskara, Daniel; Silintowe, Yunita Budi Rahayu (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2025)
Advanced technology enables trade transactions through internet-linked computers and smartphones. Consequently, consumers increasingly opt for online purchases due to their practicality. Impulse buying is expected to occur when consumers search for product information online. However, not all consumers make impulse purchases easily, despite an attractive marketplace atmosphere and sales promotions. This study examines and analyzes the effects of web atmospherics and online promotions on impulse online purchasing decisions in the Shopee marketplace. Data collection was conducted using purposive sampling, focusing on young respondents who had made unplanned purchases on Shopee. The sample consisted of 198 respondents from a private university who had engaged in impulsive buying on Shopee. Multiple regression analysis (cross-sectional) was employed as the data analysis tool. The study results indicate that online sales promotions and web atmospherics exert a significant direct influence on impulse online purchasing among young consumers. Among these factors, web atmospherics have a stronger effect, as they enhance the ease of navigating the marketplace platform.